Professional Ethics of Legal Advisors or Advocates when Proceeding in Court - Permata, Chusnul Qotimah Nita; Haidarrani, Ananda; Sumbowo, Eri Bambang Budi (Amsir Law Journal, 2022)
This study aims to determine the professional ethics of a legal advisor or advocate when proceeding in court. This study uses a quantitative approach. Data were collected using the document study method conducted by the author. The conclusion can be stated that the advocate profession, in which the concept of an advocate is an officer of the court or in the language of Law Number 18 of 2003 concerning Advocates, an advocate is a law enforcer. As a law enforcer, upholding ethics from the perspective of the advocate profession is very contextual and therefore the next discussion will be followed on how the position and role of the advocate professional organization in upholding the ethics. Professional organizations have a Code of Ethics that imposes obligations and at the same time provides legal protection to each of its members in carrying out their profession. Advocates as a respectable profession who in carrying out their profession are under the protection of the law, the law and the Code of Ethics must maintain the image and dignity of the honor of the profession, as well as be loyal and uphold the Code of Ethics and Professional Oath, whose implementation is supervised by the Honorary Council. The Indonesian Advocate Code of Ethics is the highest law in carrying out the profession, which guarantees and protects but imposes an obligation on every advocate to be honest and responsible in carrying out their profession, especially when proceeding in court.